Die Sprache der Bilder : Eine Studie zur ikonographischen Exegese der anthropomorphen G̲tterbilder im Zoroastrismus - Farridnejad, Shervin (Iranica., 2018)
According to a widely held opinion in research, Zoroastrian art did not exist in ancient Iran. In "The Language of Images", Shervin Farridnejad examines representations of ancient Iranian anthropomorphic deities and their appearance in the Zoroastrian pantheon using the methodical approach of an exegetical iconography. Farridnejad traces the representation and development of the Zoroastrian idols and analyzes the origin of their iconography within the Iranian religious imagery, especially in the interplay with the religious ideas preserved in the written tradition. In his comprehensive and richly illustrated study, the author dedicates himself to the sometimes complex images of gods, which played a major role as multi-layered carriers of meaning in the religious life of the ancient Zoroastrians. In addition, he determines general formal structures, illuminates their genesis and researches the "seat in life" of the images of gods, taking into account the literary tradition of the Zoroastrian corpus in Avestan and Middle Persian. Farridnejad thus offers for the first time a comprehensive, methodologically sound overview of the Zoroastrian imagery in the context of the religion and culture of pre-Islamic Iran